Sistemas agroflorestais e seus efeitos sobre os atributos químicos em Argissolo Vermelho-Amarelo do Cerrado piauiense - Iwata, Bruna de F.; Leite, Luiz F. C.; Araujo, Ademir S. F.; Nunes, Luis A. P. L.; Gehring, Christoph; Campos, Liliane P. [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2012)
This study aimed to quantify the effects of agroforestry systems (AFS), with different periods of adoption, and slash and burn agriculture (SB) on the chemical attributes of an Ultisol in the 'Cerrado' of Piaui State, Brazil. In two distinct climatic seasons (dry and rainy) four systems were studied: AFS with six (AFS6) and thirteen years (AFS13) of adoption, an area under SB and a native forest (NF), as a reference. In the AFS, in all depths, higher reduction in the Al3+ and H+ + Al3+ contents were observed as well as an increase of pH value and contents of nutrients (N, P, Ca, Mg and K) and organic carbon in soil. In the soil under SB, only in superficial layers, the ash deposited on the soil caused an increase in contents of nutrients, except for P, which was higher in all the depths. There was significant seasonal effect in the contents of nutrients, reducing in the rainy season. Agroforestry systems promoted increase in the nutrient contents of an Ultisol and can be considered useful to improve soil chemical quality in areas of 'Cerrado' of Piau State, Brazil.
Agroforestry systems and its effects on chemical attributes of an Ultisol in the 'Cerrado' of Piaui State, Brazil
Keywords: soil conservation; soil quality; sustainable management